Posibles actuaciones económicas en la crisis actual a partir de las diferencias de opinión entre expertos - Maria Carmen Lozano Gutiérrez; Federico Fuentes Martín (Atlantic Review of Economics, 2011)
– In this paper is carry out an analysis of affinities in the perception on how to leave the crisis behind. For that we have considered the opinion of experts belonging to the politics, the economy, the company and the banking in order to gather those opinions and to look for likeness and differences in their answers. The applied methodology might be useful in searching solutions according to the maximum consensus among experts and therefore being of some help for taking any decision.
Keywords: A12; C15; C61; 330; crisis; taking decisions; fuzzy Logic; Wirtschaftskrise; Entscheidung bei Risiko; Fuzzy Sets